(untitled) (Research, Society and Development, 2024)
Human resource management in healthcare plays a crucial role in service quality and professional satisfaction, directly impacting the efficiency and effectiveness of healthcare systems. This study aimed to analyze and synthesize approaches and practices in human resource management within the sector, focusing on identifying key challenges, strategies, and trends that could enhance organizational performance and service quality. To this end, an integrative literature review was conducted using the database SciELO, PubMed, and Medline, employing specific descriptors connected through Boolean operators. The research was temporally delimited and followed inclusion and exclusion criteria for article selection, resulting in 12 scientific studies that supported the proposed discussion. The findings highlight the importance of adopting practices that promote continuous development and employee well-being, fostering a healthier work environment that reflects operational efficiency and patient safety.